Optical measurement of physiological sodium currents in the axon initial segment. (6th November 2020) - Filipis, Luiza; Canepari, Marco
Abstract : Key points: Τhe axonal Na + fluorescence underlying an action potential in the axon initial segment was optically measured at unprecedented temporal resolution. The measurement allowed resolution of the kinetics of the Na + current at different axonal locations. The distinct components of the Na + current were correlated with the kinetics of the action potential. NEURON simulations from a modified published model qualitatively predicted the experimentally measured Na + current. The present method permits the direct investigation of the kinetic behaviour of native Na + channels under physiological and pathological conditions. Abstract: In most neurons of the mammalian central nervous system, the action potential (AP) is generated in the axon initial segment (AIS) by a fast Na + current mediated by voltage‐gated Na + channels. While the axonal Na + signal associated with the AP has been measured using fluorescent Na + indicators, the insufficient resolution of these recordings has not allowed tracking the Na + current kinetics underlying this fundamental event. In this article, we report the first optical measurement of Na + currents in the AIS of pyramidal neurons of layer 5 of the somatosensory cortex from brain slices of the mouse. This measurement was obtained by achieving a temporal resolution of 100 μs in the Na + imaging technique, with a pixel resolution of 0.5 μm, and by calculating the time‐derivative of the Na + change corrected for longitudinal diffusion. We identified a subthreshold current before the AP, a fast‐inactivating current peaking during the rise of the AP and a non‐inactivating current during the AP repolarization. We established a correlation between the kinetics of the non‐inactivating current at different distances from the soma and the kinetics of the somatic AP. We quantitatively compared the experimentally measured Na + current with the current obtained by computer simulation of published NEURON models, demonstrating how the present approach can lead to the correct estimate of the native behaviour of Na + channels. Finally, we discuss how the present approach can be used to investigate the physiological or pathological function of different channel types during AP initiation and propagation. Key points: Τhe axonal Na + fluorescence underlying an action potential in the axon initial segment was optically measured at unprecedented temporal resolution. The measurement allowed resolution of the kinetics of the Na + current at different axonal locations. The distinct components of the Na + current were correlated with the kinetics of the action potential. NEURON simulations from a modified published model qualitatively predicted the experimentally measured Na + current. The present method permits the direct investigation of the kinetic behaviour of native Na + channels under physiological and pathological conditions.